Interactions between silicon and alkaloid defences in endophyte‐infected grasses and the consequences for a folivore. (9th November 2021) - Cibils‐Stewart, Ximena; Mace, Wade J.; Popay, Alison J.; Lattanzi, Fernando A.; Hartley, Susan (Sue) E.; Hall, Casey R.; Powell, Jeff R.; Johnson, Scott N.
Abstract: Grasses have developed a wide range of morphological and physiological mechanisms to resist herbivory. For instance, they accumulate silicon (Si) in tissue, as physical defence, and associate symbiotically with foliar Epichloë ‐endophytes that provide chemical defence via antiherbivore alkaloids. Recent evidence showed that some Epichloë ‐endophytes increase foliar Si in forage grasses; however, whether this impacts insect herbivores is unknown. Furthermore, while Si is primarily a physical defence, it also affects production of plant defensive secondary metabolites; Si supply might therefore affect Epichloë ‐alkaloids, although this remains untested. We grew endophyte‐free (Nil) and Epichloë ‐infected tall fescue and perennial ryegrass in a factorial combination with or without Si supplementation, in the absence or presence of Helicoverpa armigera . Epichloë ‐endophyte strains were AR584 for tall fescue, and AR37, AR1 or Wild‐type (WT) for perennial ryegrass. We assessed how Si supply and Epichloë ‐endophytes in interaction with herbivory affected foliar Si and mutualist‐derived alkaloid concentrations. Subsequently, their effects on H. armigera relative growth rates (RGRs) were evaluated. Endophytes generally increased Si concentrations in Si‐supplied plants. In tall fescue AR584 and perennial ryegrass AR37, endophytes increased constitutive (herbivore‐free) and induced (herbivore‐inoculated) Si concentrations by at least 25%; in contrast, in perennial ryegrass, the AR1 endophyte only increased constitutive levels. Si supply did not affect alkaloids produced by AR584 or AR1/WT endophytes; however, in the presence of herbivory, Si supply decreased the induction of alkaloids produced by AR37 endophytes by 33%. For tall fescue, Si supply reduced H. armigera RGR by at least 76%, regardless of endophytic status, whereas, endophyte‐alkaloids played a secondary role only reducing herbivore growth in the absence of Si supply. Conversely, in perennial ryegrass, both Si and endophyte‐alkaloids (regardless of Si supply) reduced herbivore RGR although not synergised. Novel interactions between constitutive and induced Si‐ and alkaloid‐based antiherbivore defences in grasses were observed. Overall, Si had a greater effect on the folivore than endophytes in both grasses. Endophyte defences contributed more to herbivore resistance in perennial ryegrass than tall fescue. We demonstrate that Si and endophytes were not antagonistic and highlight that the protective nature of their interaction varies with the grass‐endophyte species tested. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.